Psychological problems of wives who have not been blessed with education by using reality counseling - Martina Timbu (Education and Social Sciences Review, 2021)
Marriage is the only legitimate means for building a household and giving birth to offspring, in line with human nature. (Indra, 2004). The purpose of marriage by a husband and wife is to form a happy family, the presence of the baby in the family is placed at the very top level of marital duties, namely to damage the side of the family. In reality, not all couples can easily obtain offspring as expected. The situation of couples who have been married for more than six years without contraception and do not have it is called infertility. Conditions of childless marriages often result in conflicts between husband and wife. The wife / woman is more often accused of being the main cause because the process of conceiving and giving birth is attached to the nature of women. Women who are always blamed will result in psychological problems in the form of stress or depression, feelings (low self-esteem) and negative thoughts about God. The purpose of discussing this case is to find out what psychic programs the wife has yet to obtain and that efforts are being made to overcome them. To obtain the data needed in this study, researchers used a reality approach, the subject of this study was a wife who did not have offspring who were married for more than six years. The results of this discussion follow the process of counseling thoughts, feelings and behaviors to receive